The Influence of Marketing Mix and Consumer Satisfaction on Consumer Loyalty at Bukalapak - Khanha Putra, Wayan; Putu Widhia Rahayu, Ni (International Journal of Social Science, Education, Communication and Economics, 2024)
The development of the business world in the field of online shop sales is increasing and competition is increasing rapidly, so entrepreneurs must be able to provide what consumers need as a basis for consumer decisions. This research is intended to reveal the impact of marketing promotion tactics and the level of customer satisfaction on the Bukalapak platform, which will ultimately influence consumer loyalty at Bukalapak. This study applies quantitative methods by utilizing descriptive analysis as the main tool. The information collection process is carried out through the distribution of survey instruments. The objects that are the focus of this research are active Bukalapak users. Referring to the Slovin formula, it is revealed that the minimum number of participants required is 100 individuals. Based on the findings obtained from this exploration, it can be concluded that the Marketing Mix Variable (X1) provides good or positive results and is quite significant on Consumer Loyalty (Y). The Consumer Satisfaction variable (X2) has a positive and significant effect on Consumer Loyalty (Y), then together the Marketing Mix and Consumer Satisfaction variables measurably have a good, positive and clearly significant effect on the Consumer Loyalty variable. Researchers have several suggestions, namely that companies should further improve aspects of the marketing mix so that the goals set by the company can be realized as quickly as possible. Then the company can increase the level of service, promotions and other strategies to maintain and increase the level of consumer satisfaction.